Characterization and classification of dairy herds using multivariate analysis in Costa Rica. - Vargas-Leitón, Bernardo; Solís-Guzmán, Oscar; Sáenz-Segura, Fernando; León-Hidalgo, Héctor (Agronomía Mesoamericana, 2013)
This study was carried out to characterize and classify a group of herds (n=1086) associated to the main Dairy Cooperative in Costa Rica. The information analyzed in this study was obtained initially from the last census conducted by the cooperative during year 2007. This information was complemented with computerized records of the same cooperative and geographical information systems with climatic and soil types data. Farm classification was performed by combining two different multivariate techniques: Factor Analysis (FA) and Cluster Analysis (CA). Analysis was performed on 18 variables, mainly related to physical and climatic aspects, herd management, input level and production level. FA identified three significant principal factors: intensification level, altitude (masl), and productive orientation accounting for 42,6%, 24,2% and 13,2% of total variance. On the basis of these three factors, CA identified five main herd typologies: Intensive specialized dairy herds in the highlands (n=374), Semi-intensive specialized dairy herds in the highlands (n=274), Intensive specialized dairy herds in the Lowlands (n=167), Extensive specialized dairy farms in the Lowlands (n=189) and Extensive Dual-Purpose herds in the Lowlands (n=82).